Understanding MSME Tax Compliance: The Role of Mental Accounting, Tax Awareness, Sanctions, and Socialization in Bekasi - Hazmi, Raldin Alif Al; Aribowo, Irwan (Universitas Negeri Semarang, 2025)
Purpose: The study aims to analyze the influence of mental accounting, tax awareness, tax sanctions, and tax socialization on individual tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Bekasi Regency. The research specifically focuses on MSMEs operating within Bekasi Regency as the object of study. Method: A quantitative research approach was applied using primary data collected through questionnaire surveys distributed to MSME actors. A total of 147 valid responses were analyzed using the Structural Equation Model - Partial Least Squares (SEM-PLS) method. Findings: The analysis revealed that mental accounting, tax sanctions, and tax socialization significantly influence tax compliance. Conversely, tax awareness does not show a significant effect on tax compliance among MSME taxpayers in Bekasi Regency. Novelty: The research underscores the importance of psychological dimensions and tax-related education, alongside regulatory frameworks, in influencing tax compliance behavior. The exploration of mental accounting as a variable remains limited within the Indonesian context, particularly concerning MSMEs. Therefore, this study aims to enrich the existing body of tax literature by addressing this gap, specifically in relation to MSME compliance in Indonesia. The outcomes of this study provide both theoretical contributions and practical recommendations for policymakers especially the Directorate General of Taxes in formulating more targeted and effective strategies to improve tax compliance among MSMEs nationwide.